3D printed human organoids: High throughput system for drug screening and testing in current COVID‐19 pandemic. Issue 10 (7th July 2022) - Parihar, Arpana; Pandita, Vasundhara; Khan, Raju
Abstract: In the current pandemic, scenario the world is facing a huge shortage of effective drugs and other prophylactic medicine to treat patients which created havoc in several countries with poor resources. With limited demand and supply of effective drugs, researchers rushed to repurpose the existing approved drugs for the treatment of COVID‐19. The process of drug screening and testing is very costly and requires several steps for validation and treatment efficacy evaluation ranging from in‐vitro to in‐vivo setups. After these steps, a clinical trial is mandatory for the evaluation of treatment efficacy and side effects in humans. These processes enhance the overall cost and sometimes the lead molecule show adverse effects in humans and the trial ends up in the final stages. Recently with the advent of three‐dimensional (3D) organoid culture which mimics the human tissue exactly the process of drug screening and testing can be done in a faster and cost‐effective manner. Further 3D organoids prepared from stems cells taken from individuals can be beneficial for personalized drug therapy which could save millions of lives. This review discussed approaches and techniques for the synthesis of 3D‐printed human organoids for drug screening. The key findings of the usage of organoids for personalized medicine for the treatment of COVID‐19 have been discussed. In the end, the key challenges for the wide applicability of human organoids for drug screening with prospects of future orientation have been included. Abstract : 3D bioprinting of lung organoids and its application to study the mechanism of infection, the process of host‐microbe interaction, drug/vaccine screening and to assess therapeutic response.